The Impact of Education on Personality - Evidence from a German High School Reform - Sarah Dahmann; Silke Anger (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2015)
This paper investigates the short-term effects of a reduction in the length of high school on students' personality traits using a school reform carried out at the state level in Germany as a quasi-natural experiment. Starting in 2001, academic-track high school (Gymnasium) was reduced from nine to eight years in most of Germany's federal states, leaving the overall curriculum unchanged. This enabled students to obtain a university entrance qualification (Abitur) after a total of only 12 rather than 13 years of schooling. We exploit the variation in the length of academic-track high school over time and across states to identify the effect of schooling on students' Big Five personality traits and on their locus of control. Using rich data on adolescents and young adults from the German Socio-Economic Panel (SOEP) study, our estimates show that shortening high school caused students on average to be more extroverted and less emotionally stable. Our estimates point to important heterogeneous effects. In addition to differences between East and West Germany, we find that male students and students from disrupted families showed stronger personality changes following the reform: they became more agreeable and more extroverted, respectively. We conclude that the educational system plays an important role in shaping adolescents' personality traits.
Keywords: I21; I28; J24; 330; Non-cognitive Skills; Big Five; Locus of Control; Skill Formation; High School Reform